Influence of Dimethylsulfoxide and Dioxygen in the Fructose Conversion to 5-Hydroxymethylfurfural Mediated by Glycerol's Acidic Carbon - Tudino, Tatiane C.; Nunes, Renan S.; Mandelli, Dalmo; Carvalho, Wagner A. (Frontiers in Chemistry, 2020)
Both the catalytic production of 5-hydroxymethylfurfural (5-HMF) from carbohydrates and the use of a catalyst obtained from residues stand out for adding value to by-products and wastes. These processes contribute to the circular economy. In this work it was evaluated optimized conditions for 5-HMF production from fructose with high yield and selectivity. The reaction was catalyzed by an acidic carbon obtained from glycerol, a byproduct of the biodiesel industry. Special attention has been given to the use of dimethyl sulfoxide (DMSO) as a solvent and its influence on system activity, both in the presence and absence of O2. Glycerol's carbon with acidic properties can be effectively used as catalyst in fructose dehydration, allowed achieving conversions close to 100% with 5-HMF selectivities higher than 90%. The catalyst can be reused in consecutive batch runs. The influence of DMSO in the presence of O2 should be considered in the catalytic activity, as the stabilization of a reaction intermediate by the [O2:DMSO] complex is favored and, both fructose conversion and 5-HMF yield increase.